2001
DOI: 10.1053/jpro.2001.27338
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory strength of glass ionomer and zinc phosphate cements

Abstract: Purpose: The present in vitro study examined 3 mechanical properties, namely compressive, flexural, and diametral tensile strength, of various commercially available cements and core materials as a function of time after mixing. Materials and Methods: The examined materials were 2 cermet cements (Ketac Silver [ESPE, Seefeld, Germany] and Chelon Silver [ESPE]), 1 metal-reinforced glass ionomer cement (Miracle Mix [GC Dental Industrial Corp, Tokyo, Japan]), 2 conventional glass ionomer cements (Ketac Bond [ESPE]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
4
1
1
Order By: Relevance
“…It has been reported that the diametral tensile strength of the two metal‐reinforced glass ionomer‐based core materials (Ketac‐Silver GIC and GC Miracle Mix GIC) were 12.51 ± 2.22 and 9.71 ± 3.10 MPa, respectively 25 . These values were higher than the values for conventional glass ionomers, 34 yet less than half of the values for the resin composite core materials used in this study. As expected, the fracture strengths of the glass ionomer‐based core materials Ketac‐Silver GIC and GC Miracle Mix GIC were statistically lower than those of the resin‐based core materials used in this study by at least 49% for the same dowel design.…”
Section: Discussioncontrasting
confidence: 48%
“…It has been reported that the diametral tensile strength of the two metal‐reinforced glass ionomer‐based core materials (Ketac‐Silver GIC and GC Miracle Mix GIC) were 12.51 ± 2.22 and 9.71 ± 3.10 MPa, respectively 25 . These values were higher than the values for conventional glass ionomers, 34 yet less than half of the values for the resin composite core materials used in this study. As expected, the fracture strengths of the glass ionomer‐based core materials Ketac‐Silver GIC and GC Miracle Mix GIC were statistically lower than those of the resin‐based core materials used in this study by at least 49% for the same dowel design.…”
Section: Discussioncontrasting
confidence: 48%
“…Under the same testing conditions, Ketac Molar yielded 85.3 ± 32.5 MPa for the compressive strength. The study by Piwowarczyk et al 26 was concerned primarily with the compressive, flexural, and tensile strengths of zinc phosphate and glass ionomer cements. In that study, the metal‐reinforced glass ionomer cement Ketac Silver™ (3M ESPE) showed results similar to Ketac Molar under the same testing conditions as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…An impression was made of this margin section with Enamel 60-90 [26] 41 [33] 400 [27] 10 [33] Dentin 245-280 [26] 18.6 [33] 297 [27] 11.4 [33] Vitablocs [28] 6.3 [29] 80 (24h) [28] 35 [33] a polyvinyl-siloxane impression material (President light body, Coltène, Altstätten, Switzerland) and replicas prepared for quantitative margin analysis in a scanning electron microscope (SEM). Thereafter, molars were stored in tap water at room temperature for at least two weeks before entering the thermo-mechanical cycle.…”
Section: ###mentioning
confidence: 99%
“…Selfadhesive resin-based cements however, show favorable results of marginal adaptation [23] and mechanical support [24,25] of all-ceramic posterior crowns. The question arises whether self-adhesive resin-based cements are able to provide adequate marginal adaptation and strength for esthetic ceramic CAD/CAM crowns with their particular physical properties [26][27][28][29][30][31][32][33][34]. We hypothesized that there would be no difference between resin-bonded crowns and those cemented with self-adhesive resinbased cement with regard to marginal adaptation and strength of ceramic CAD/CAM crowns after extensive thermo-mechanical fatigue stress with dentinal liquid pressure maintained.…”
Section: Introductionmentioning
confidence: 99%